Perencanaan dan Implementasi Photostock TK Tabgha di Yayasan Tabgha - Christine Christine; Deli Deli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
The purpose of this paper is to improve the quality of archival photos of Excellent Holykids Kindergarten in terms of social media content. Photography has become important as a visual communication tool in the era of technological advancement and the increasing need for information. The way we communicate and get information has been changed by social media. One of the problems of Excellent Holykids Kindergarten is the lack of sufficient photo archive for social media content. This report provides a solution through a Model Development Cycle (MDLC) approach to improve the quality of the school photo archive and document children's learning activities, as visual documentation is essential to provide a positive image of the school. There are 195 photos edited with a warm tone theme and the results will be organized in Google Drive for easy collaboration with school partners and use in social media content.